Assessment of reproductive hormones levels in Iraqi pre- pubertal autistic children - OMAR F. ABDUL- RASHEED (International Journal of Pharma and Bio Sciences, 2016)
The prevalence of autism is 1in 300 children in the US. Autism is characterized by impairments is social relatedness and communication, repetitive behaviors, abnormal movement patterns, and sensory dysfunction. There is some evidence that reproductive hormones may play a role in the pathophysiology of autism. The objective of this study is to investigate the role of reproductive hormones in pre- pubertal children with autism.A case- control study was conducted between June 2015 and October 2015 in the Department of Chemistry and Biochemistry, College of Medicine, Al- Nahrain University, Baghdad, Iraq. The study was performed on 60 pre- pubertal male children with autism recruited from the Pediatric Department of Al- Sader General Hospital, Baghdad, Iraq. The levels of luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin (PRL), inhibin B and free testosterone (fT) were measured by Enzyme- linked immunosorbent assay (ELISA) technique in the sera of these pre- pubertal autistic male patients and categorized as mild, moderate and severe (20 patients each) and was compared with 26 age- sex matched control subjects. The data of this study indicate that there was a significant elevation (p= 0.010) of plasma free testosterone level (6.34±0.30 pg/mL) in pre- pubertal autistic children group compared to age- sex matched healthy children (3.12 ±0.55 pg/mL). Plasma luteinizing hormone (LH) and follicle stimulating hormone (FSH) were significantly decreased in pre- pubertal autistic children group in comparison with control group (P= 0.038, P= 0.044 respectively). Plasma free testosterone (fT) level were elevated significantly (p = 0.005) in severe autistic patients in comparison with control group.Plasma free testosterone level was significantly elevated in pre- pubertal autistic children in comparison with non- autistic control group and this elevation may be attributed to altered androgen biosynthetic pathway rather than structural pituitary anomalies.